2017
DOI: 10.1515/intox-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Animal tests for anxiety-like and depression-like behavior in rats

Abstract: An animal model of human behavior represents a complex of cognitive and/or emotional processess, which are translated from animals to humans. A behavioral test is developed primarily and specifically to verify and support a theory of cognition or emotion; it can also be used to verify a theory of a psychopathology, but it is not developed for a particular type of psychopathology. The paper reviews tests commonly used in novel drug discovery research. Focus is especially on tests which can evaluate anxiety-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 31 publications
2
120
2
Order By: Relevance
“…We observed that the extracts treatment exhibited protective effect against depression and prevented the hormone dysregulation. Depression induced rats showed reduced sucrose preference, rearing, crossing and increased immobility time, which agrees with findings of other researchers (Belovicova et al 2017;Liu et al 2013). These results serve as evidence for the successfulness in induction of Neuroendocrine disorder is closely associated with stress induced depression.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that the extracts treatment exhibited protective effect against depression and prevented the hormone dysregulation. Depression induced rats showed reduced sucrose preference, rearing, crossing and increased immobility time, which agrees with findings of other researchers (Belovicova et al 2017;Liu et al 2013). These results serve as evidence for the successfulness in induction of Neuroendocrine disorder is closely associated with stress induced depression.…”
Section: Discussionsupporting
confidence: 92%
“…This was different from the group with per oral treatment, all of which showed a decline (F=28.576; df=4.18; p<0.01). Immobile behaviour on FST indicates despair in rodents when it realized its effort to escape from the tank is in vain, and this behaviour constitutes synonymous behaviour observed in depressed humans (Belovicova et al, 2017). Amitriptyline treatment as an antidepressant caused a decrease in the duration of immobility.…”
Section: Forced Swim Testmentioning
confidence: 99%
“…Both male and female rats showed increased depression as measured by a preference for water rather than chocolate milk. There was no depression detected in mice treated from GD 14-17 after assessment using the forced swim test (Belovicova, Bogi, Csatlosova, & Dubovicky, 2017;Venerosi et al, 2010) (Table S3).…”
Section: Abbreviationsmentioning
confidence: 99%